Environmental effectiveness of the cross compliance Standard 4.6 Minimum livestock stocking rates and/or appropriate regimens - Sepe, Lucia; Salis, Mauro; Francaviglia, Rosa; Fedrizzi, Marco; Carroni, Antonio Melchiorre; Sabia, Emilio; Bruno, Annarita; Rufrano, Domenico; Ruda, Paola; Dell'Abate, Maria Teresa; Alianello, Alberto; Veloccia, Marco; et al. (Italian Journal of Agronomy, 2015)
The paper presents the main results of the monitoring on the effectiveness of the cross compliance Standard 4.6 Minimum livestock stocking rates and/or appropriate regimes carried out in two case studies within the project MO.NA.CO: sheep grazing in medium-rich pastures in southern Apennines and in the plain of Sardinia, Italy. The monitoring involved aspects related to soil, flora, livestock and economics (competitiveness differential). The study showed, although in the short term, that the minimum stocking rate 0.2 LU/ha/year was not effective and, conversely, the effectiveness of the maximum level of stocking rate (4 LU/ha) for the maintenance of the habitat. The generalization in applying minimum and maximum rate, not taking into account the climatic conditions, forage resources or farming system (including the species of grazing animal) may lead to a serious nullification of the conditions of the Standard. The authors recommend to identify homogeneous areas and eligible specific stocking rates from all Italian regions, also considering the animal species.